A Craniomaxillofacial Surgical Assistance Workstation for Enhanced Single-Stage Reconstruction Using Patient-Specific Implants. Issue 8 (November 2016) - Murphy, Ryan J.; Liacouras, Peter C.; Grant, Gerald T.; Wolfe, Kevin C.; Armand, Mehran; Gordon, Chad R.
Abstract : Background: Craniomaxillofacial reconstruction with patient-specific, customized craniofacial implants (CCIs) is ideal for skeletal defects involving areas of aesthetic concern—the non-weight-bearing facial skeleton, temporal skull, and/or frontal-forehead region. Results to date are superior to a variety of "off-the-shelf" materials, but require a protocol computed tomography scan and preexisting defect for computer-assisted design/computer-assisted manufacturing of the CCI. The authors developed a craniomaxillofacial surgical assistance workstation to address these challenges and intraoperatively guide CCI modification for an unknown defect size/shape. Methods: First, the surgeon designed an oversized CCI based on his/her surgical plan. Intraoperatively, the surgeon resected the bone and digitized the resection using a navigation pointer. Next, a projector displayed the limits of the craniofacial bone defect onto the prefabricated, oversized CCI for the size modification process; the surgeon followed the projected trace to modify the implant. A cadaveric study compared the standard technique (n = 1) to the experimental technique (n = 5) using surgical time and implant fit. Results: The technology reduced the time and effort needed to resize the oversized CCI by an order of magnitude as compared with the standard manual resizing process. Implant fit was consistently better for the computer-assisted case compared with the control by at least 30%, requiring only 5.17 minutes in the computer-assisted cases compared with 35 minutes for the control. Conclusion: This approach demonstrated improvement in surgical time and accuracy of CCI-based craniomaxillofacial reconstruction compared with previously reported methods. The craniomaxillofacial surgical assistance workstation will provide craniofacial surgeons a computer-assisted technology for effective and efficient single-stage reconstruction when exact craniofacial bone defect sizes are unknown. Abstract : Supplemental Digital Content is available in the text